2021
DOI: 10.1039/d1em00123j
|View full text |Cite
|
Sign up to set email alerts
|

Refinement and extension of COSMO-RS-trained fragment contribution models for predicting the partition properties of C10–20 chlorinated paraffin congeners

Abstract: New COSMO-RS-trained fragment contribution models provided quantum chemically based predictions for a range of chlorinated paraffin congener groups and mixtures regarding partition properties and their temperature dependence.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…However, as might be expected, the log K OW values predicted from EPISuite for all possible isomers are similar, ranging between 5.8 and 7.5, with a mean value of 6.4. Sophisticated quantum mechanical calculations by Endo and Hammer and Endo also showed that there is a similarly narrow range of log K OW values for short-chain PCA isomers. These values reflect the uncertainty that is introduced when a single randomly selected isomer is used to represent the behavior of the entire elemental composition group.…”
Section: Results and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, as might be expected, the log K OW values predicted from EPISuite for all possible isomers are similar, ranging between 5.8 and 7.5, with a mean value of 6.4. Sophisticated quantum mechanical calculations by Endo and Hammer and Endo also showed that there is a similarly narrow range of log K OW values for short-chain PCA isomers. These values reflect the uncertainty that is introduced when a single randomly selected isomer is used to represent the behavior of the entire elemental composition group.…”
Section: Results and Discussionmentioning
confidence: 89%
“…EPISuite employs a QSPR model that produces the same logK AW value regardless of isomeric structure. However, the results of Endo and Hammer 35 and Endo 36 suggest that the distribution of logK AW values of isomers is also quite narrow, with standard deviations of ∼0.4 for all short-chain PCAs considered in their study. All computed parameters, ranges, means, and standard deviations (errors) of all the possible structures of C 10 H 18 C1 4 are summarized in Table S1.…”
Section: Experimental Methodsmentioning
confidence: 85%
“…Physicochemical properties (including equilibrium phase partition ratios and atmospheric and biodegradation half-lives) of C 10 –C 30 CP homologues were predicted with quantitative structure–property relationships (Text S1.7). Activation energies for degradation in air, water, and solid were assumed to be 10, 30, and 30 kJ/mol following Krogseth et al, and heats of phase transfer for C 10–20 CP congeners were taken from Endo . For each homologue, the CiP-CAFE modeling was done based on the physicochemical properties of the most abundant congener in the homologue in technical mixtures or environmental samples.…”
Section: Methodsmentioning
confidence: 99%
“…Can LCCPs be global pollutants? Almost all LCCP homologues possess log octanol–air partition coefficients (log K OA ) in excess of 11 . This suggests that they will be primarily associated with particles in the atmosphere and less subject to long-range atmospheric transport.…”
Section: Introductionmentioning
confidence: 95%
“…Almost all LCCP homologues possess log octanol−air partition coefficients (log K OA ) in excess of 11. 20 This suggests that they will be primarily associated with particles in the atmosphere and less subject to long-range atmospheric transport. Model predictions of long-range atmospheric transport indicate that SCCPs belong to the persistent organic chemicals that are most likely to accumulate in the Arctic, while LCCPs with log K OA > 11 will accumulate to a much lesser extent.…”
Section: ■ Introductionmentioning
confidence: 99%